Peningkatan Keterampilan Menulis Teks Pidato melalui Model Problem Based Learning Untuk Siswa Kelas VI SDN Cengkareng Timur 15 Pagi Jakarta - Fikra Hawa Aulia Fikra Hawa Aulia; Khusnul Fatonah (UNIB Press, 2024)
This study was motivated by the low skills of students in writing speech texts properly and correctly, especially in class VI students of SDN Cengkareng Timur 15 Pagi Jakarta. The purpose of this study was to improve the skill of writing speech text through Problem Based Learning model for grade VI B students at SDN Cengkareng Timur 15 Pagi Jakarta. This research is a classroom action research conducted collaboratively. This research was conducted in two cycles, each cycle consisting of planning, implementation, observation, and observation. Data collection techniques were carried out by observation, tests, and documentation. The data analysis technique used was qualitative observation analysis technique. The results showed that the Problem Based Learning model could improve the speech writing skills of grade VI students of SDN Cengkareng Timur 15 Pagi Jakarta. The results of cycle I explained that the average percentage of teacher activities was 89.05%. Meanwhile, the results of the second cycle observations explained that the average percentage of teacher activities was 95.31%. Then the percentage of student activities amounted to 92.18%. Then in cycle I the results of the speech writing skills test got an average score of 62.50 with a percentage of student completeness of 60%. Then increasing the results of the speech writing skills test in cycle II got an average score of 76.61 with a percentage of student completeness of 80%.